Design of a Web-Based Internal Claim Audit Application in the Casemix Unit in a Hospital to Minimize Pending Claims - Yastori Yastori; Nurul Fitri Khumaira; Muhammad Kaddafi Suyatno; Nik Azliza Nik Ariffin (Jurnal Infokes, 2026)
The Casemix Unit plays a strategic role in the submission and reimbursement of healthcare service claims for BPJS Kesehatan participants. Nevertheless, many hospitals continue to experience pending claims due to administrative errors, incomplete documentation, coding inaccuracies, prolonged verification processes, policy changes, and limited integration of information systems. This study aimed to design and evaluate a web-based internal claim audit application to improve verification effectiveness and reduce pending claims in the Casemix Unit. This research adopted a Research and Development (R&D) approach using the Borg and Gall model and was conducted over one year at RSU Prof. Dr. M. A. Hanafiah Batusangkar, where an increasing number of pending claims was identified in 2024. System evaluation was carried out through usability assessment, and comparative observation of the claim audit process before and after prototype implementation. The results demonstrated that all application features functioned according to system requirements. Implementation of the application contributed to improved operational efficiency, enhanced accuracy in document and coding verification, and faster claim review time compared to the previous manual process. The application includes document completeness verification, coding validation, claim status monitoring, and AI-assisted early detection of potential errors with corrective recommendations. These findings indicate that the system is feasible and capable of supporting a more structured and consistent internal audit process. The study concludes that the application has strong potential to improve claim management quality and support hospital financial sustainability. Future studies should conduct broader implementation, integrate the system with hospital information systems and BPJS platforms, and perform long-term quantitative evaluations of its effectiveness.